Rancangan Teknis Reklamasi Lahan Bekas Penambangan Sirtu di Desa Trosono, Kecamatan Parang, Kabupaten Magetan - Larasati, Indah; Hakim, Abdul; Yusrianti, Yusrianti; Pribadi, Arqowi; Utama, Teguh Taruna (Dampak, 2023)
This study aims to assess the land damage caused by mining activities in the village of Trosono, Parang District, Magetan Regency, and to determine the plan for the reclamation of ex-mining land, namely by restoring the function of the ex-mining mining land according to its designation according to the Regional Regulation of Magetan Regency Number 15 of 2012 as production forest land and plantations. Based on the evaluation of land damage criteria that have been carried out on topography, soil, and vegetation conditions, 75% of these parameters are still feasible to be used as forest and plantation areas. The existing condition of the ex-situ mining area based on the results of surveys and field mapping, there are remnants of cliffs as high as 9.5 m where the slope is almost perpendicular to the bottom of the excavation. The planned reclamation activities include land surface arrangement by adjusting the geometry of the slopes with a maximum cliff height of 3 m,  a terrace width of 2.1 m, and a slope angle of 30o at the end of the mining. Plants planned for revegetation are sengon and ginger with a spacing of 2 m x 3 m and ginger spacing of 0.3 m x 0.6. The dimensions of the sengon planting space used are 0.4 m x 0.4 m x 0.4 m and for ginger plants 0.3 m x 0.3 m x 0.3 m. With mathematical calculations, it is planned that the number of seeds of sengon plants to be planted is 56 seeds and 9.833 seeds of ginger plants. Keywords: ex-situ, ginger, mining, plantation, sengon  ABSTRAK Penelitian ini bertujuan untuk mengkaji kerusakan lahan akibat kegiatan penambangan di Desa Trosono Kecamatan Parang Kabupaten Magetan, serta menentukan rencana reklamasi lahan bekas tambang yaitu dengan mengembalikan fungsi lahan bekas tambang. sesuai peruntukannya menurut Peraturan Daerah Kabupaten Magetan Nomor 15 Tahun 2012 sebagai kawasan hutan produksi dan perkebunan. Berdasarkan evaluasi kriteria kerusakan lahan yang telah dilakukan terhadap kondisi topografi, tanah, dan vegetasi, 75% dari parameter tersebut masih layak untuk dijadikan kawasan hutan dan perkebunan. Kondisi eksisting area penambangan ex situ berdasarkan hasil survei dan pemetaan lapangan terdapat sisa-sisa tebing setinggi 9,5 m yang kemiringannya hampir tegak lurus dengan dasar galian. Kegiatan reklamasi yang direncanakan meliputi penataan permukaan tanah dengan menyesuaikan geometri lereng dengan tinggi tebing maksimal 3 m, lebar teras 2,1 m, dan sudut kemiringan lereng 30o di ujung penambangan. Tanaman yang direncanakan untuk revegetasi adalah sengon dan jahe dengan jarak tanam 2 m x 3 m dan jarak tanam jahe 0,3 m x 0,6. Dimensi ruang tanam sengon yang digunakan adalah 0,4 m x 0,4 m x 0,4 m dan untuk tanaman jahe 0,3 m x 0,3 m x 0,3 m. Dengan perhitungan matematis, direncanakan jumlah bibit tanaman sengon yang akan ditanam sebanyak 56 bibit dan 9.833 bibit tanaman jahe. Kata kunci: ex-situ, ginger, mining, plantation, sengon